(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food adulteration is a global issue and underdeveloped countries are more vulnerable to it due to a lack of monitoring and legislation. Food adulteration has been a source of concern since the dawn of civilization as it not only lowers the quality of food products but also has a number of negative health consequences. However, this is one of the most widespread phenomenon that has gone unnoticed in many countries. Unfortunately, contrary to popular assumption for milk adulterants can offer major health risks leading to lethal infections. This study provides a full discussion of common milk adulterants as well as various methods for detecting the adulterants both qualitatively and statistically. Concerns about food safety and regulation have resulted in the development of several approaches for adulterant detection in food, such as physical, biochemical/immunological and molecular techniques. This study is structured to be an ’adulterant-based’ study rather than a ’techniques-based’ one, with qualitative detection methods enlisted for the majority of frequent adulterants and quantitative detection methods limited to a few key milk adulterants. Aside from standard procedures, significant advancements in these detection techniques have also been reported. This review aims to add to the body of information about potential milk adulterants and detection methods.